In vitro and in vivo characterization of anthrax anti-protective antigen and anti-lethal factor monoclonal antibodies after passive transfer in a mouse lethal toxin challenge model to define correlates of immunity - Staats, Herman F; Alam, S Munir; Scearce, Richard M; Kirwan, Shaun M; Zhang, Julia Xianzhi; Gwinn, William M; Haynes, Barton F (Infection and immunity, 2007)
Passive transfer of antibody may be useful for preexposure prophylaxis against biological agents used as weapons of terror, such as Bacillus anthracis. Studies were performed to evaluate the ability of anthrax antiprotective antigen (anti-PA) and antilethal factor (anti-LF) neutralizing monoclonal antibodies (mAbs) to protect against an anthrax lethal toxin (LeTx) challenge in a mouse model and to identify correlates of immunity to LeTx challenge. Despite having similar affinities for their respective antigens, anti-PA (3F11) and anti-LF (9A11), passive transfer of up to 1.5 mg of anti-PA 3F11 mAb did not provide significant protection when transferred to mice 24 h before LeTx challenge, while passive transfer of as low as 0.375 mg of anti-LF 9A11 did provide significant protection. Serum collected 24 h after passive transfer had LeTx-neutralizing activity when tested using a standard LeTx neutralization assay, but neutralization titers measured using this assay did not correlate with protection against LeTx challenge. However, measurement of LeTx-neutralizing serum responses with an LeTx neutralization assay in vitro employing the addition of LeTx to J774A.1 cells 15 min before the addition of the serum did result in neutralization titers that correlated with protection against LeTx challenge. Our results demonstrate that only the LeTx neutralization titers measured utilizing the addition of LeTx to J774A.1 cells 15 min before the addition of sample correlated with protection in vivo. Thus, this LeTx neutralization assay may be a more biologically relevant neutralization assay to predict the in vivo protective capacity of LeTx-neutralizing antibodies.